2020
DOI: 10.1007/s11224-020-01536-6
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the inhibitory potential of selective phytochemicals against Mpro of 2019-nCoV: a computer-aided study

Abstract: At the end of December 2019, a novel strain of coronavirus, given the name of 2019-nCoV, emerged for exhibiting symptoms of severe acute respiratory syndrome. The virus is spreading rapidly in China and around the globe, affecting thousands of people leading to a pandemic. To control the mortality rate associated with the 2019-nCoV, prompt steps are needed. Until now there is no effective treatment or drug present to control its life-threatening effects in the humans. The scientist is struggling to find new in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 32 publications
(30 reference statements)
1
19
0
1
Order By: Relevance
“…These energies can characterize the electrophilic or nucleophilic nature of a compound. Therefore, the screened phytochemicals illustrated the higher reactivity of these phytochemicals, as reported in various previous studies [ 23 25 , 27 , 30 33 , 35 , 52 , 65 ].…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…These energies can characterize the electrophilic or nucleophilic nature of a compound. Therefore, the screened phytochemicals illustrated the higher reactivity of these phytochemicals, as reported in various previous studies [ 23 25 , 27 , 30 33 , 35 , 52 , 65 ].…”
Section: Resultssupporting
confidence: 80%
“…Repurposing of drugs is a remarkable approach to opt antiviral compounds as COVID-19 drug candidates [ 57 ]. Recently, a study has been reported targeting the main protease of SARS-CoV-2, using a set of phytochemicals [ 30 ]. However, herein, another set of phytochemicals has been used to target MTase and helicase.…”
Section: Resultsmentioning
confidence: 99%
“…The intermediate is mixed with p-toluenesulfonyl chloride and triethylamine to activate the acid function, followed by the addition of reagent (74) in a one-pot procedure. The condensation allows the formation of intermediate (75), which is submitted to acidic conditions for a Boc deprotection, followed by another nucleophilic additionelimination reaction with reagent (76), thus obtaining the final product ritonavir (2) ( Fig. 16).…”
Section: Patent Protection and Synthesis Of Repositionable Drugsmentioning
confidence: 99%
“… 68 , 70 , 73 M pro has been widely explored in drug discovery campaigns using experimental and/or computational approaches. 68 , 73 , 74 , 75 , 76 , 77 Moreover, M pro has no human homologue, which reduces the chances of toxic effects of a given inhibitor. 68 Potential SARS-CoV-2 M pro inhibitors include FDA-approved antivirals, such as inhibitors of HIV-1 [e. g., lopinavir (1) /ritonavir (2)] and HCV [e.g., boceprevir (3)] proteases, as well as antineoplastic [e.g.…”
mentioning
confidence: 99%
“…Docking simulation was repeated. During virtual screening with AutoDock Vina 4.2 complex formation was achieved by allowing all rotatable bonds of the chemical ligands free choice of torsional degrees of freedom and Rapid Grid-Based (RGB) energy evaluation (Rasool et al, 2020).…”
Section: Active Site Predictionmentioning
confidence: 99%